2016
DOI: 10.3109/01480545.2015.1123267
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of JAK2, STAT3 and Akt1 proteins by granulocyte colony stimulating factor following carbon monoxide poisoning in male rat

Abstract: Carbon monoxide (CO) is an odorless, colorless, tasteless and non-irritating by-product of inefficient combustion of hydrocarbon fuels such as motor vehicle exhausted gases. It is the leading cause of mortality in the USA among all unintentional toxicants. Male rats exposed to CO poisoning in the heart has many cardiovascular effects such as, cardiomyopathy, tachycardia, arrhythmias, and ischemia and in severe cases, myocardial infarction (MI) and cardiac arrest. Cardiomyocyte apoptosis is one of the most freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In a study done by Gang Lu and colleague, it was shown that global ischemia increases BAX/BCL2 ratio (Lu et al, 2006). Furthermore, several reports have confirmed that CO poisoning results in induction of apoptosis (Ghorbani et al, 2017;Hashemzaei et al, 2016b;Weaver, 2009). Our findings are consistent with the data obtained in other studies because CO poisoning induces global ischemia and RES can reduce apoptosis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a study done by Gang Lu and colleague, it was shown that global ischemia increases BAX/BCL2 ratio (Lu et al, 2006). Furthermore, several reports have confirmed that CO poisoning results in induction of apoptosis (Ghorbani et al, 2017;Hashemzaei et al, 2016b;Weaver, 2009). Our findings are consistent with the data obtained in other studies because CO poisoning induces global ischemia and RES can reduce apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study showed that RES could ameliorate CO‐induced cardiovascular effects in an animal model (Hashemzaei et al , ). In order to find new substances that can fight the deleterious effects of CO poisoning in the heart and brain and also to shed light on the underlying mechanisms, in our previous studies, we discussed the involved pathways (Ghorbani et al , ; Hashemzaei et al , ; Mohamadpour et al , ). To the best of our knowledge, it is for the first time that the neuroprotective effect of multiple‐dose RES administration on CO poisoning is evaluated in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, G-CSF therapy led to cardiac protection due to its effect on increasing phosphorylated proteins. In addition, G-CSF reduces transcription of apoptosis-inducing proteins such as Bad and caspase 3 [ 19 ] It is expected that after MI about one-half of all patients develop CHF and is characteristic for acute changes in LV function [ 20 ]. Accordingly, G-CSF can improve the function of a chronic failed heart.…”
Section: Preclinical and Clinical Studies Evaluating G-csf Effectivenmentioning
confidence: 99%
“…Natural products are small molecules produced by organisms as primary and secondary metabolites and they exert various useful properties including anti-oxidant, anti-inflammatory, cancer preventive, cardiovascular, anti-Alzheimer's, platelet modulatory and pain relief effects (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%